Aspek Sosial Ekonomi pada Sistem Agroforestri di Areal Kerja Hutan Kemasyarakatan (HKm) Kabupaten Lampung Barat, Provinsi Lampung - Puspasari, Eny; Wulandari, Christine; Darmawan, Arief; Banuwa, Irwan Sukri (Jurnal Sylva Lestari, 2017)
Community Forest (HKm) is one of the schemes of Social Forestry, in which the management of its working area implements the agroforestry system. This study aims to determine the structure of income and farmer welfare, agroforestry contribution to farmer income and the factors that influence the income of farmers who do agroforestry in HKm working area. The study was conducted at the Group of HKm Bina Wana, Rigis Jaya II and Mitra Wana Lestari Sejahtera, West Lampung District. The results show that agroforestry activities contribute to farmer income of 66% and the rest from other sectors. Based on income from agroforestry activities it is known that 93% of farmers are in the prosperous category. Factors that significantly affect farmers' income are the area of cultivated land, the number of plant species that have been produced and the training followed by the farmers. In accordance with the provisions of the farmers' land area within the HKm area is no longer possible to be expanded, therefore farmers should enrich with more types of multi-use plants and follow training to increase knowledge so that land management is more optimal to increase revenue. Keywords: agroforestry, income, the contribution of income, income factors, welfare level